The green monster - Murphy, Sonia; George, Chris, 1977- (New York : Simon Spotlight, 2004)
Casey helps Michaelangelo and Donatello keep a nosey television monster-hunter from revealing their existence.
D., unk., c2000
005-007.
Keywords: Turtles -- Fiction; Heroes -- Fiction; Monsters -- Fiction